Hierarchical power and personality in leader-member exchange. Issue 7 (12th September 2016) - Yoon, David J.; Bono, Joyce E.
Abstract : Purpose: The purpose of this paper is to examine the role of supervisor and subordinate personality in high quality supervisor-subordinate (leader-member exchange; LMX) relationships. Design/methodology/approach: In this field study, 142 supervisors drawn from a leadership development program, and 509 of their subordinates, completed a personality survey and reported on the quality of their relationships. Findings: Self and partner personality (agreeableness and extraversion), and the match between them were predictors of LMX. Consistent with approach/inhibition theory of power, personality traits of relationship partners had a stronger effect when the partner held a position of power (i.e. supervisors) than when the partner was a subordinate. Practical implications: The results inform organizational selection by showing the importance of supervisory traits for the formation of high quality supervisor-subordinate relationships. They may also help organizations facilitate the development of high quality supervisory relationships. The findings also suggest that it is critical to consider the balance of power when assessing LMX, along with factors that lead to its development, or benefits that ensue from it. Originality/value: To date, there is an assumption that certain traits predict the development of high quality relationships between supervisors and subordinates. The results point out the importance of considering the role of power in LMX relationships. The paper shows that the effects of supervisory traits, which are rarely examined in the context of LMX relationships, more strongly predict LMX than do the traits of subordinates.